Development of Metapragmatic Reflections on the Function of Verbal Irony in Adolescents - Hess Zimmermann, Karina (2022)
Objective. Analyse metapragmatic reflections made by adolescents aged 12 and 15 years old (16 per age group) on the functions of verbal irony, in two types of ironic speech acts: ironic thanking and ironic offering. Method. The participants faced eight stories ending with ironic remarks, and through questioning, they were asked about the functions they attributed to the ironic statements. Results. Significant differences are shown due to age, but none related to the type of statement, which confirms that the ability to make metapragmatic reflections on verbal irony develops late in children’s language.